The Right Tool Is What They Need, Not What We Have: A Taxonomy of Appropriate Levels of Precision in Patient Risk Communication. (February 2013) - Zikmund-Fisher, Brian J.
While patients often receive risk information, exactly what constitutes being "informed" about health risks is often unclear. Patients have specific needs, such as avoiding being surprised by a possible outcome and making complex risk trade-off decisions. Yet all risk information is not equally informative for those needs. In this article, I present a taxonomy of seven risk concepts that vary in their inherent precision and evaluability. Congruent with the "less is more" concept, I argue that risk communications should use formats that are tailored to message recipients' specific informational needs. Simpler formats can be used when patients only need to order risks, while more complex numerical probability statements will be necessary when patients need to assess differences in risk magnitude and put those differences into meaningful context. Selecting need-congruent formats when designing communications about risks to patients is a novel approach that may better support patients' health care decision making.